Phage diversity from shrimp ponds underpinning multi-host lytic activity in Vibrio pathogens - ANANDA SEKAR KINANTI; ASEP AWALUDIN PRIHANTO; YOGA DWI JATMIKO; FARHID HEMMATZADEH; RAHMI NURDIANI (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Kinanthi AS, Prihanto AA, Jatmiko YD, Hemmatzadeh F, Nurdiani R. 2025. Phage diversity from shrimp ponds underpinning multi-host lytic activity in Vibrio pathogens. Biodiversitas 26: 4457-4464. Vibrio parahaemolyticus is a major cause of seafood-related foodborne illness that has developed significant antibiotic resistance, creating an urgent need for effective and safer control management.  This study aims to isolate and characterize lytic bacteriophages capable of inhibiting a broad spectrum of foodborne pathogenic bacteria. Bacteriophages were isolated from shrimp shell and pond wastewater samples, following a methodical approach that included bacteriophage isolation, density testing, confirmation, and host range testing. The results indicate that V. parahaemolyticus was successfully isolated from dead shrimp. The lytic bacteriophages, designated ?ALT (from pond wastewater) and ?KU (from shrimp shells), were lysed their bacterial hosts, with activity detectable up to a dilution of 10??. This suggests that even at low concentrations, the phages could effectively lyse their bacterial targets. Both bacteriophages were found to exhibit a multi-host range, effectively lysing several pathogenic species such as Vibrio alginolyticus, Vibrio cholerae, Vibrio harveyi, and Aeromonas hydrophila, while not affecting Salmonella Typhi, Pseudomonas aeruginosa, or Acinetobacter baumannii. Transmission Electron Microscopy (TEM) revealed that ?ALT has a hexagonal shape, while ?KU has an icosahedral shape. These findings highlight the potential of these bacteriophages as effective biocontrol agents in managing foodborne pathogens, offering a safer and more targeted alternative to antibiotics. Future molecular characterization is required to further understand these bacteriophages mechanism of action and improve their application in food safety.